Analisa Alogaritma Layout Heuristik untuk Meminimasi Total Material handling dalam Perencanaan Tata Letak Fasilitas - Annisa Kesy Garside (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This research has goal to compare there alternative layout performances CRAFT,MULTIPLE, and BLOCPLAN. Using the problem of layout which include forward flow material and fordward backward flow material can be found result : Multiple Algoritm has total distance and material cost minimally but the problems that have lower departement,CRAFT algoritm can be used better than MULTIPLE algoritm because almost gives the same result with easier input process.